Studi Tentang Hubungan Sikap Dengan Upaya Ibu Dalam Pemberian Imunisasi Dasar Pada Anak Di Kawasan Pesisir Dan Kepulauan Tatinang - Windatania Mayasari; Harmiyati Harmiyati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2021)
Immunization is one of intervention to give immune for the baby/child with the procedure input vaccine into the body so the body could make antibody against to disease spesificly. Immunization services for baby/child at tatinang have not yet reached Universal Child Immunization. It was mean more than 90% had achieved. They are BCG (50%), DPT (40%), Hepatitis B (20%), Polio (60%) and Campak (10%). The aim of this research to know sttitude related to mother’s effort for giving immunization in children at tatinang. This research is analysis description with cross sectional study. All of mothers who have child 12-23 month at tatinang, as respondent have taken by total sampling (30 respondent) and used chi-square with significant level ?=0,055. Result of research has showed that there was relationship between attitude p=0,000. For respondent to more interesting in giving immunization for children base on their ages to protection from some disease